Review of ’Lesbian, Gay, Bisexual and Trans* Individuals Living with Dementia: Concepts, Practice and Rights’ edited by Sue Westwood and Elizabeth Price - Johnston, Tim R. (Age, Culture, Humanities: An Interdisciplinary Journal, 2020)
—